Dinamika Resiliensi Komunitas terkait Dampak Penggusuran Jalan Tol YIA di Padukuhan Timpang, Kulon Progo - Ardyayu Diva Norvelina; Anggi Rahajeng (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Pengasih Sub-District is one of the sub-districts in Kulon Progo that will be affected by the eviction of the Solo-Yogyakarta-Yogyakarta International Airport (YIA) toll road which involved several hamlets including Jamus, Derwolo, Kepek, Clawer, Tunjungan, and Ngento. The evictions can have an impact on decreasing the welfare of the community as shown through the psychological resilience of the residents. This study aims to provide a forum for residents to express feelings, thoughts, and views. In addition, it also provides understanding and information regarding strategies for managing emotions and resilience. This research is applied research based on action research by providing educational information. Data collection was carried out through observation, interviews, psychological resilience instrument scales, and the dynamics of Focus Group Discussion (FGD). The results of the study stated that the condition of the people affected by the evictions tended to feel sad about the conditions that had occurred but already had plans for the future so they felt comfortable. The causal factors for this condition are seen from the financial aspect, place of residence, memories, education, and family welfare. This appliedresearch on the outreach program for emotional management and resilience can provide new insights to residents about the problems they are experiencing so that later residents do not feel alone in facing problems and can motivate one another. In addition, material related to strategies for managing emotions and resilience can also be implemented in daily life in the future.